Tradisi Ancak Agung sebagai Arena Komunikasi Sosial - Fasadena, Nova Saha (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The Ancak Agung tradition represents one of the enduring religious and social rituals preserved by the Madurese community as an expression of gratitude and solidarity. This study aims to understand Ancak Agung as an arena of social communication that reflects the power relations, habitus, and cultural capital of its supporting community. Employing Pierre Bourdieu’s theory of social practice, this research examines how individuals and groups interact and interpret their social positions through symbols, rituals, and participation within the tradition. The study adopts a descriptive qualitative approach, utilizing participatory observation and in-depth interviews with religious leaders, committee members, and ritual participants. The findings reveal that Ancak Agung functions not only as a medium of worship and thanksgiving but also as an arena for the reproduction of cultural capital and the reinforcement of communal-religious habitus. Through symbolic practices and social communication, the values of love, mutual cooperation, and interfaith tolerance naturally flourish, affirming the tradition as an instrument of social harmony within the framework of Islam Nusantara